Analisis Kesalahan Berbahasa Indonesia Dalam Ejaan Mahasiswa Pg Paud - Paulus Novento; Nia Devianna Laura Br Tarigan (STIKes Ibnu Sina Ajibarang, 2024)
This research aims to analyze language errors in the spelling of preschool students. In the student's thesis abstract, writing errors were found. Students' mistakes when writing their thesis abstracts are sometimes not using the correct Indonesian spelling. The method used in this research is a qualitative descriptive method and data collection procedure techniques in the form of observation. Based on the research results, the samples taken were 7 abstract data and student books at Medan State University, Early Childhood Education Teacher Education Study Program. In writing abstracts there is language spelling that is not correct according to the Enhanced Indonesian Spelling (EYD) guidelines, namely in the use of prepositions, use of capital letters, writing full stops, use of italics and errors in writing words. There are 7 spelling error data contained in the abstracts and PGPAUD student books. Based on the results of the discussion above, it can be concluded that the author is inaccurate in using language spelling in capital letters, italics, words with affixes, use of abbreviations, use of punctuation.